Model-based damage detection, localization and assessment of structures the extended system identification methodology - Natke, Hans Günther; Yao, James T.P. (Zielona Góra: Uniwersytet Zielonogórski)
System analysis and system identification are the basis of damage detection, localization and assessment. The (global) dynamic mathematical model with generally many fewer degrees of freedom than the static model is used for stability and dynamic qualification. It is also the basis for identification, which refers to the correction and validation of the mathematical model by using measurements of the existing structure.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka